The Concept of Rehabilitation Law for Military Personnel Who Commit Narcotics Crimes in the Perspective of Legal Certainty - Salam, Abdul (Journal of Law and Social Politics, 2025)
Background: Narcotics abuse among Indonesian National Armed Forces (TNI) members raises legal and human rights concerns. Although Law No. 35 of 2009 recognizes rehabilitation as a right for narcotics addicts, in practice TNI personnel are often directly subjected to dismissal without rehabilitation, creating legal injustice and human rights issues Objective: This study aims to analyze the regulatory framework, implementation, and ideal concept of rehabilitation for TNI members involved in narcotics crimes from legal, criminological, rehabilitation, and human rights perspectives Methods: This research employs a normative juridical method with a qualitative approach by examining laws, military regulations, and legal doctrines relevant to rehabilitation and military discipline Results: The findings show that rehabilitation for TNI members is not optimally implemented due to disharmony between civil and military law, the absence of special rehabilitation facilities for soldiers, and weak internal TNI regulations. As a result, punitive measures are often prioritized over rehabilitative efforts, despite rehabilitation’s purpose of restoring health, rights, and dignity Conclusion: The study concludes that effective rehabilitation for TNI personnel requires harmonization of civil and military legal frameworks, the establishment of specialized military rehabilitation centers, and stronger internal regulations. A holistic, rights-based rehabilitation approach is essential to address narcotics abuse fairly while maintaining discipline and strengthening the integrity of the TNI.